A new species and a new record of Bolbitius (Bolbitiaceae, Agaricales) from Scotland and Britain, respectively - Drummond-Herdman, Alfred; Malysheva, Ekaterina; Jakob, Sigrid; Szafián, Dorottya Anna; Nagy, László G. (Phytotaxa, 2025)
A new coprophilous species of Bolbitius, B. corrugatus sp. nov., is described and illustrated based on collections from Scotland. The new species is characterised by its yellow, corrugated pileus, hexagonal spores, and coprophilous habitat. A phylogenetic analysis based on ITS and LSU was conducted to support morphological data. A link to a time-lapse video showing the growth of basidiocarps in the type collection is included as part of the description. Another coprophilous species, B. excoriatus, is introduced as new to Britain and is included in the phylogenetic analysis. Morphological descriptions, illustrations, and phylogenetic analysis results of the two species are provided. A competition-based hypothesis is proposed for the variation in basidiocarp size among coprophilous fungi.